ANALISIS PROGRAM GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) DENGAN ORGANISASI PERANGKAT DAERAH (OPD) DI KEC. SIANTAR BARAT KOTA PEMATANGSIANTAR TAHUN 2020 - anna rosita (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Changes in the pattern of disease (epidemiological transition) are characterized by increased deaths and morbidity due to PTM that have an impact on increasing the financing of health services that must be borne by the community and government as well as decreasing productivity of the people of Pematangsiantar City. is expected to be overcome by implementing GERMAS in Pematangsiantar City. This research is a descriptive qualitative research that aims to analyze the GERMAS Program with Regional Apparatus Organizations in Kecamatan Siantar Barat, Pematangsiantar City in 2020. The selection of informants uses snowball sampling techniques. The informants in this study were 4 people, each representing representatives from the Regional Apparatus Organization, the Salimah Women's Community Organization , PHBS cadres and the Community of Kecamatan Siantar Barat. The results showed that the Regional Organization, Salimah Women's Community Organization and PHBS cadres supported the implementation of the GERMAS in Kec. Siantar Barat, Pematangsiantar City. The obstacle in implementing GERMAS is the low awareness of the community to participate in the implementation of GERMAS. It is hoped that the Regional Apparatus Organization, the Salimah Women's Community Organization, PHBS cadres remain committed in providing support for the implementation of the GERMAS and the community is expected to be more active in socialization activities and other GERMAS programs. to increase knowledge about the importance of applying GERMAS in everyday life.